2007 International Conference on Mechatronics and Automation 2007
DOI: 10.1109/icma.2007.4303908
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Independently Rotating Wheels for Railway Vehicles

Abstract: It is well known that conventional wheelsets have disadvantages of potential oscillatory instability above critical speed as a result of solid coupling between two wheels. Independently rotating wheels can overcome this disadvantage but may loss the natural guidance which solid axis linked wheels have. This paper presents an experimental study of independently rotating wheels which adopt active wheel driven for high speed railway vehicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 8 publications
0
15
0
2
Order By: Relevance
“…Also, when the disturbance occurs, one side created greater torque to recover lateral displacement. Because the lateral displacement occurred close to the right side, the front wheel according to (3) showed increasing torque of right motor, and the rear wheel showed increasing torque of the left side motor. This could be shown in the Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, when the disturbance occurs, one side created greater torque to recover lateral displacement. Because the lateral displacement occurred close to the right side, the front wheel according to (3) showed increasing torque of right motor, and the rear wheel showed increasing torque of the left side motor. This could be shown in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, lateral restoring force control for sharp curve drive of independently rotating wheel suspension is the core technology of the low-depth urban railway system. [3][4][5][6][7] In this paper, a control of the lateral displacement restoring force for sharp curved drive of the shallow-depth subway systems is proposed. The drive torque, steering torque command were made to execute this research to increase the stable drive performance without contacting the flange in the curved-railroad.…”
Section: Introductionmentioning
confidence: 99%
“…These are then used to provide traction, wheel guidance and stability control. The motors can be externally mounted and connected to the wheelset through a gearbox (Pérez et al [137], Liang et al [139,140], Ahn et al [141], Lu et al [142] and Farhat et al [98,143]) as shown in Fig. 30 or embedded inside the wheels (Mei et al [144], Ji et al [145] and in the 'Next Generation Train' project in [124], [146][147][148][149]).…”
Section: (B) Driven Independently Rotating Wheel (Dirw)mentioning
confidence: 99%
“…4 Stability control simulation and experimental research by 1/5 scale independently driven wheel test rig was implemented based on yaw feedback control. 5,6 Although several active control schemes have been proposed for independently rotating wheels, some fundamental problems still need to be solved satisfactorily. One of the key issues for the control system is the measurement difficulty in the feedback signal.…”
Section: Introductionmentioning
confidence: 99%